2024
DOI: 10.1039/d4fb00004h
|View full text |Cite
|
Sign up to set email alerts
|

Computational modeling for the enhancement of thermosonicated Sohphie (Myrica esculenta) fruit juice quality using artificial neural networks (ANN) coupled with a genetic algorithm

Puja Das,
Prakash Kumar Nayak,
Radha krishnan Kesavan

Abstract: Sophie fruits are antioxidant-rich and reducing chronic disease risk. Optimization of TS parameters using ANN maximized the yield and bioactive compounds. TS is promising for large-scale juice extraction, enhancing market competitiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…PSO is a population-based meta-heuristic optimization algorithm motivated by the cooperative behavior of foraging animals such as flocks of birds or schools of fish. , Multiple linear regression (MLR) is a statistical analysis method used in machine learning. Few studies are using these methods for juice optimization. The combination of RSM, MLR, and PSO can provide more accurate results in component optimization in vegetable juices. When the literature was scanned, no studies were found investigating the optimization of parsley juice’s chlorophyll and ascorbic acid components with RSM, MLR, and PSO after ultrasound application.…”
Section: Introductionmentioning
confidence: 99%
“…PSO is a population-based meta-heuristic optimization algorithm motivated by the cooperative behavior of foraging animals such as flocks of birds or schools of fish. , Multiple linear regression (MLR) is a statistical analysis method used in machine learning. Few studies are using these methods for juice optimization. The combination of RSM, MLR, and PSO can provide more accurate results in component optimization in vegetable juices. When the literature was scanned, no studies were found investigating the optimization of parsley juice’s chlorophyll and ascorbic acid components with RSM, MLR, and PSO after ultrasound application.…”
Section: Introductionmentioning
confidence: 99%